Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4274/balkanmedj.2015.1809
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacterial Resistance Patterns of Pediatric Urinary Tract Infections and Rationale for Empirical Antibiotic Therapy

Abstract: Background:The causative agent spectrum and resistance patterns of urinary tract infections in children are affected by many factors.Aims:To demonstrate antibiotic resistance in urinary tract infections and changing ratio in antibiotic resistance by years.Study Design:Retrospective cross-sectional study.Methods:We analysed antibiotic resistance patterns of isolated Gram (-) bacteria during the years 2011-2014 (study period 2) in children with urinary tract infections. We compared these findings with data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…In the present study, the proportion of UTI was significantly higher in females (73%) than in males (27%). Our results were consistent with other studies that showed that UTI was more frequent in females [ 5 , 13 , 15 , 16 ]. High frequency of UTI in females can be due to anatomical differences such as shortness of urethra and close space between the anus and urethral orifice [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the proportion of UTI was significantly higher in females (73%) than in males (27%). Our results were consistent with other studies that showed that UTI was more frequent in females [ 5 , 13 , 15 , 16 ]. High frequency of UTI in females can be due to anatomical differences such as shortness of urethra and close space between the anus and urethral orifice [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…agalactiae was very sensitive to ceftriaxone. Our findings of high resistance rate to cephalosporines are significantly and agreeing with other studies in Iran (Ranjbar et al, 2009), and Turkey (Gökçe et al, 2017).…”
Section: Zanco Journal Of Pure and Applied Sciences 2019supporting
confidence: 93%
“…Whereas in a research done in Istanbul, 61% of patients were female (1.5 girls: 1 boy) and the average age was 3 years and 9 months. (15) Women made up the majority of respondents in a research carried out in Kashmir. Our research found that 76.4% of participants responded well to Fosfomycin, whereas 54.5 % responded favourably to ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%